THE Weed chemical control in grain sorghum at the steppe zone of Ukraine - Tkalich, Yuri; Tsyliuryk , Oleksandr; Havryushenko, Oleksandr; Mytsyk , Oleksandr; Kozechko , Volodymyr; Rudakov , Yuriy; Tkalich, Olga; Honchar, Natalia (Ecological Questions, 2023)
The highest control of ragweed (Ambrosia artemisiifolia L.) in the field experiments was provided by the herbicide Primekstra TZ Gold (effect - 83%; dose - 4.5 l/ha), bent sedum (Amaranthus retroflexus L.) with herbicide Mastak (effect - 88%; dose - 0.5 l/ha), chicken millet (Echinochloa crus-galli L.) using the herbicides Varyag and Datonit Gold (effect - 57%, dose - 4.5 and 2.5, respectively), white quinoa (Chenopodium album L.) – herbicide Datonite Gold with surfactant (effect - 85%; dose - 2.5 l/ha). The greatest chemical control was provided by the application options of herbicides Varyag – 4.5 l/ha and Agent – 0.6 l/ha in the phase of 3-5 leaves of the crop in June. This treatment provide the Ponki sorghum hybrid grain yield increase 24-27% compared to the control.